Optimal timing of antenatal corticosteroids in women with bleeding placenta previa or low-lying placenta. (18th June 2019) - Alsayegh, Eman; Barrett, Jon; Melamed, Nir
Abstract: Background: Administrating a single course of antenatal corticosteroids to women at risk of preterm birth between 24 and 34 weeks of gestation has been shown to decrease neonatal morbidity and mortality. There is evidence that the optimal timing for the administration of antenatal corticosteroids is within 1–7 days before birth as the effect of antenatal corticosteroids has been shown to decline 7 days after administration. Therefore, given that antenatal corticosteroids are the single most effective intervention in cases of preterm birth, efforts should be made to optimize the timing of administration of antenatal corticosteroids. Objective: To test the hypothesis that the timing of antenatal corticosteroids in women with vaginal bleeding due to placenta previa or low-lying placenta can be optimized by identifying women at low risk of imminent delivery. Study design: This was a retrospective cohort study of all women admitted to a tertiary referral center at 24–34 weeks' gestation with vaginal bleeding due to placenta previa or low-lying placenta between 2003 and 2014. Multivariable logistic regression analysis was used to identify factors that are independently associated with delivery within 14 days from admission. Results: A total of 202 women who met the inclusion criteria were admitted with vaginal bleeding in the presence of placenta previa or low-lying placenta during the study period, of whom 31 (15.3%) and 44 (21.8%) gave birth within 7 and 14 days from admission, respectively. The following factors were independently associated with delivery within 14 days from admission: complete placenta previa (odds (OR) 3.57, 95%CI 1.57–9.03), severe bleeding at presentation (OR 17.14, 95%CI 2.92–100.70), uterine contractions at presentation (OR 6.02, 95%CI 1.91–19.00), and cervical length <25 mm at presentation (OR 6.33, 95%CI 1.37–29.11). A predictive test based on the presence of ≥1 of these risk factors was associated with a sensitivity of 90.9% and a negative predictive value of 94.6% for delivery within 14 days of presentation. Conclusions: In women presenting with vaginal bleeding due to placenta previa or low-lying placenta, it seems possible to identify a subgroup of women in whom the likelihood of delivery within 14 days is low. This information may allow for selective (rather than routine) administration of antenatal corticosteroids in this scenario, and may thereby contribute to the optimization of the timing of administration of antenatal corticosteroids.